Komunikasi Antar Budaya Pertukaran Pelajar Universitas Binadarma Palembang dan University Selangor Malaysia - Rizka Nadiyah Rahmah Safhirah; Desy Misnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Behavior, interaction, and aculturation of intercultural communication in students of Communication Sciences University of Binadarma and University of Cultural Sciences Selangor Malaysia are the subject of this research. Using student exchange programmes to enhance mutual cultural understanding and understanding, this intercultural communication is facilitated through introduction, adaptation, symbolic interactionalism, and cultural accuracy. The author hopes to improve inter-cultural communication through methods such as cultural identification, adaption, and accuration. The writer uses qualitative methods and performs interviews with several students of Selangor University Malaysia to answer various questions. The results of this study show that his friends of different cultures have very intense intercultural communication. In places like cafés, lobbies, halls, classrooms, seats, and campus courts, people show their culture. Readers get literature about intercultural communication with new students who have cultural differences because the same cases happen every year. This is the benefit of this research.